2y=-3x

Simple and best practice solution for 2y=-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2y=-3x equation:


Simplifying
2y = -3x

Solving
2y = -3x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Divide each side by '2'.
y = -1.5x

Simplifying
y = -1.5x

See similar equations:

| 9+x/3=-10 | | v+25=77 | | (7/12)+(5/18) | | 6/102= | | x^2+y=5x-8 | | 102/6= | | 3x-11=-17 | | 3b^2-30b=6b-60 | | (a+2)/2=-1 | | 2x-4/6=6x+2/x-6 | | (-16/11)/(4/9) | | x^2+y+8=5x | | (-1/15)+(-14/15) | | 6x+30=25x-20 | | 2x^2-12x+36= | | d*d+18(d+4)=-9 | | s*s-3(s+2)=4 | | 0=-7.5(x^2-4x-320) | | 5r-15/12r2+24r*6r+12/30-10r | | r=-7.5(x^2-4x-320) | | 2x=16y | | 7*(2/3) | | 5-4y+y=-23 | | x/10+30=45 | | x^3+8x^2-3x-52=0 | | k^3-6k^2-27k=0 | | -3(u+5)+2=4(u+2) | | x^3+8x^2-3x=52 | | (X)=x^2+6l | | E=0.5m(0.178) | | (15/7)/(3/14) | | 4(w-1)=2(2w-3) |

Equations solver categories